Anthocyanin Compounds from Ethanol Extract of Red Fruit (Pandanus conideus L.): A Functional Group Analysis - Indah Amelia Rizky; Angga Bayu Budiyanto; Lukman Hardia (Jurnal Penelitian Pendidikan IPA, 2024)
Red Fruit (Pandanus conoideus L.) is a typical Papuan plant that is rich in bioactive compounds such as anthocyanins, which have the potential to act as antioxidants. This research aims to analyze the chemical structure of anthocyanin compounds from red fruit ethanol extract using Fourier Transformed Infrared (FTIR) spectroscopy. FTIR is a spectroscopic tool widely used to characterize or detect functional groups and qualitatively identify compounds in samples. Anthocyanins act as antioxidants and have various biological activities such as preventing cancer, cardiovascular disease, and diabetes. Extraction was carried out using the maceration method using 70% ethanol solvent, and characterization was performed using FTIR in the wave range 4000-450 cm⁻¹. The results of the research that has been carried out show that the ethanol extract of red fruit contains secondary metabolites such as flavonoids, alkaloids, and saponins. The FTIR results of red fruit extract show the presence of functional groups characterized by the presence of the O-H, C-O-C, C-O, and C=C functional groups which are important indicators of the antioxidant properties of anthocyanins. This research confirms the potential of Red Fruit as a natural source of anthocyanins which are useful as antioxidants